Smart Parking Monitoring System Based on The Internet of Things Using Arduino and NodeMCU - I Gusti Ngurah Agung Pawana P; I Wayan Dikse Pancane; Made Widya Jayantari (TEPIAN, 2023)
Internet of Things (IoT) and smart city ecosystem, smart parking is an innovative solution that is relevant in developing a better future city. Along with the growth in the number of vehicles, parking spaces are available in public places such as development centers, airports, stations, and others whose capacity is increasingly limited. This research is to design an application and tool with the aim of arranging parking space reservations so that it is easy for drivers to get a spot. This design includes hardware and an Internet of Things connection with the designed application. This system connects IR Sensor to Arduino and NodeMCU wifi module. The NodeMCU chip consists of a SOC (system on a chip) with integrated TCP/IP protocol that allows Arduino to access the network. The cloud acts as a database to store all data related to parking areas and users who have access to the system. This component is placed in the parking area. The design results found that if there is a parked vehicle 2 LEDs will light up green, if obstructions or vehicles are not found, set to only 1 LED lit and a message is sent to the smartphone app informing them of unavailable parking. While the ultrasonic proximity sensor does not detect anything within 50 cm, on the app a white LED indicates that a parking space is available. A parking system that can provide parking location recommendations for checking sequences by a microcontroller program.